EFFECTIVENESS EVALUATION OF THE POSTGRADUATE PROGRAM IN MENTAL HEALTH COUNSELING IN UKRAINE - Joshua Kreimeyer; Olya Zaporozhets; Jacqueline Smith; Olga Lozova (Borys Grinchenko Kyiv Metropolitan University, 2020)
Ukraine is a country that has lacked access to adequately trained mental health professionals. As in other countries the development of the field of Counseling in Ukraine has some parallels to that of the US. One of the most notable parallels is the push for a better and more effective approach to mental health, driven by the impact of war, with WWII being the catalyst for refinement in the US and current war in Ukraine as the drive there. As the American Psychology Association and American Counseling Association have highlighted, the effects of trauma and unresolved problems do not need to last a lifetime. A developing initiative in Ukraine was brought by U.S.-based teams that established a postgraduate Counselor Education Program. Professional American Counselor Educators, trained in the trenches of wars abroad and representing vast ranges of experience, have volunteered their time as visiting faculty and distance supervisors. This study measures the initial progression of treatment symptomology of clients seen by Postgraduate Program in Psychological Counseling and Trauma Therapy trained Counselors. This study utilized an analysis of repeated measures over the first five sessions of counseling with the program-trained Counselor. The following measurement methods were utilized: Outcome Rating Scale (ORS), Impact Event Scale (IES-R), Beck Depression Inventory (BDI II), PTSD Checklist (PCL-5), Symptom Checklist (SCL-9). The resulting data obtained from the clients was compared to the outcomes of treatment with similarly trained therapists in the United States, United Kingdom, Australia and Denmark. Results indicated overall significance as measured on 3 out of 5 instruments (ORS, BDI-II, IES-R). The data from this sample revealed similarities to the outcomes of comparable early treatment research, conducted outside of Ukraine. These results provide a preliminary overview of how effective mental health counselors (educated by the American standards) are in mitigating client mental health symptomology. This study is a logical and necessary step in the continued development of the field of Counseling in Ukraine.